TICK-BORNE PATHOGENS DETECTION FROM TICKS INFESTING Malayopython reticulatus (REPTILIA: PYTHONIDAE) SNAKES IN INDONESIA - Supriyono Supriyono; Hana Faizah Sophia; Upik Kesumawati Hadi; Susi Soviana (BIOTROPIA, 2025)
Article Highlights:- A total of 38 ticks were collected from M. reticulatus, comprising 13 A. helvolum and 25 A. varanense.- Spotted fever group Rickettsia spp. (7.89%) and reptile-associated Borrelia sp. (2.63%) were detected in male Amblyomma helvolum ticks collected from Malayopython reticulatus snakes in Indonesia.- Snake-associated ticks may harbor emerging pathogens, underscoring the importance of tick surveillance in reptiles for early disease detection and zoonotic prevention. Abstract: Ticks are important arthropod vectors of numerous diseases in humans and animals. Furthermore, ticks are also established vectors and reservoirs of pathogens important to wildlife and human health. Rickettsia and Borrelia are two genera of bacteria that may be transmitted by ticks, and some pathogenic species are zoonosis. This research investigated the prevalence of Rickettsia spp. and Borrelia sp. in Amblyomma helvolum and Amblyomma varanense ticks fed on Malayopython reticulatus and Python bivittatus snakes in Indonesia. A total of 38 ticks were collected from three M. reticulatus snakes, while no ticks were found on the P. bivittatus snake. The 38 ticks consisted of 13 individuals A. helvolum and 25 individuals A. varanense. PCR analysis revealed that three (3/38; 7.89%) male A. helvolum ticks were positive for spotted fever group Rickettsia spp. and one (1/38; 2.63%) male A. helvolum tick was positive for a reptile-associated group Borrelia sp. Although the overall prevalence of tick-borne pathogens was low, this study underscores the importance of monitoring the prevalence and prevention of tick-borne diseases. Surveillance of ticks infesting reptiles can facilitate the early detection of disease transmission to both animals and humans. These findings also suggested that snake-associated ticks may harbor emerging tick-borne pathogens